2015
DOI: 10.5301/ejo.5000689
|View full text |Cite
|
Sign up to set email alerts
|

Tendon Elongation with Bovine Pericardium (Tutopatch®) When Conventional Strabismus Surgery is Not Possible

Abstract: Tendon elongation is a valuable addition to our strabismus surgery repertoire. However, because of duction limitations after surgery, it should be reserved for those cases in which conventional surgery is not an option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 32 publications
2
23
0
4
Order By: Relevance
“…Within the bovine pericardium, 58% received a drainage suture. It is being observed that bovine pericardium material functions as a matrix for the ingrowth of the bodies' own connective tissue (van Rijn et al 2016). A drainage suture could cause intraocular fluid to accumulate around the patch graft material and in the case of bovine pericardium limit the ingrowth of connective tissue leading to melting of the patch graft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the bovine pericardium, 58% received a drainage suture. It is being observed that bovine pericardium material functions as a matrix for the ingrowth of the bodies' own connective tissue (van Rijn et al 2016). A drainage suture could cause intraocular fluid to accumulate around the patch graft material and in the case of bovine pericardium limit the ingrowth of connective tissue leading to melting of the patch graft.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by our observation that the drainage suture tends to increase the rate of tube exposure. As in instances where bovine pericardium is not surrounded by intraocular fluid, melting of the material is not being observed (van Rijn et al 2016). In this current study, despite a trend in the survival analysis and an odds ratio of 3.45, a significant association between tube exposure and drainage sutures within the bovine pericardium cohort could not be demonstrated, however.…”
Section: Discussionmentioning
confidence: 99%
“…Weiterhin traten trotz großer Rücklagerungs-/Sehnenverlängerungsstrecken keine störenden divergenten Schielstellungen in der Nähe auf, obwohl sich die Adduktion vor allem nach Sehnenverlängerung deutlich verringerte. Inzwischen wird die Sehnenverlängerung mit bovinem Perikard auch bei anderen Erkrankungen mit großen Schielwinkeln erfolgreich eingesetzt [23,26].…”
Section: Diskussionunclassified
“…Bovines Perikard durchläuft mehrfache Fertigungsschritte, um jegliche Pathogene zu inaktivieren und Bakterien zu entfernen. Es dient als Gerüst für den zellulären Reparaturmechanismus und wird innerhalb von Wochen bis Monaten durch körpereigenes Narbengewebe ersetzt [23]. Dadurch sind weniger Nebenwirkungen, wie Abstoßung und Infektion, als bei artifiziellen, inerten Materialien zu erwarten.…”
unclassified
See 1 more Smart Citation